Comentarios críticos a la "Declaración universal sobre genoma humano y los derechos humanos" : la cuestión de la dignidad humana y la clonación - Andruet, Armando S. (Universidad Nacional de Cuyo. Facultad de Filosofía y Letras. Instituto de Filosofía., 2001)
The author discusses the indetermination of the human dignity concept that is reflected in the Universal Declaratlon on the Human Genoma and Human Rights (1996). According to this indetermination would be possible to offer the genetical material submitted to the market laws and, in the other hand, to found the human dignity only in the biochemical dimensión of the genoma.